Some new spaces of double sequences and the statistical core on l2µ(p) - Gökhan, A. (Eudoxus Press, LLC, 2014)
In this paper, we introduce the double sequence spaces (Formula Presented). The inclusion relations among these spaces are obtained. We also characterize the matrix classes (Formula Presented). Furthermore, we de.ne the statistical core of a real- valued double sequence belonging to the more general class l2µ(p) and study the statisti-cal core inequalities related to this new type of statistical core by using our matrix classes (Formula Presented). ã 2014 EUDOXUS PRESS, LLC.
Keywords: Double sequence; Double series; Statistical double limit